Fator de crescimento fibroblástico 18 (FGF18) modula a expressão de genes da via de sinalização hippo em células da granulosa bovina - Costa, Pamela Freitas (2023)
Proliferation, functional differentiation and morphological transformation of granulosa cells (GCs) are events that occur for ovarian follicular development, achieved, atresia and ovulation. There is evidence to show that GC apoptosis is the main mechanism of ovarian follicular atresia. In previous studies, it was shown that the inhibitory effect of FGF18 on steroidogenesis is similar to what occurs in atretic follicles compared to dominant follicles. Assuming that FGF18 may be involved in the process of steroidogenesis, directly affecting the expression of effectors of the Hippo signal pathway in GCs and regulating the expression of key genes that control this event, we relate the function of the Hippo signal pathway with FGF18 and a adjusting for folliculogenesis in bovine GCs and analyzing different targets of YAP1-TEAD interaction to demonstrate, in vitro, the importance of the Hippo pathway in the process of follicular divergence. In order to establish this relationship, experiments were carried out with granulosa cells from ovarian follicles of female cows from slaughterhouses. The experiments were carried out with different concentrations of FGF18 (0, 1, 10 and 100 ng/mL) controlled on the fifth day of cultivation. Granulosa cells were cultured for six days in 24-well plates at a density of 0.5x10 -6 cells per well in modified DMEN medium free of fetal bovine serum. First day of cultivation, characterized as day zero, the cells were maintained only with insulin (10 ng/mL), remaining until the first change of medium. On day two and day four of cultivation, 70% of the culture medium was changed and treatment with FSH (1ng/mL), insulin (10ng/mL) was added, and on the fifth day treatment with different concentrations was added of FGF18 (0, 1, 10 and 100 ng/ml). Observe a decrease in mRNA levels of CTGF and CYR61, specific expression genes when the YAP protein is found in the cell nucleus and the Hippo signal pathway is inactive, and a decrease in the expression of the BAX and BCL2, indicating the occurrence of cell apoptosis. STAR and CYP19 mRNA expression was not significantly different. Another important gene that it was possible to observe the reduction of mRNA expression is GFPT2, which indicates the reduction of hexosamine metabolism, an important amine for cells to be able to exercise their physiological functions and their metabolic effects. As the translocation of YAP is very dynamic, it is believed that the time of treatment of cells with FGF18 may have influenced the results obtained, as there are studies that indicate that with 12 hours of treatment there is an increase in CTGF, that is, how GCs were being treated for 24 hours it was already going into apoptosis and there was a decrease in the expression of CTGF, an external cell gene.